Estimating the health loss due to poor engagement with cardiac rehabilitation in Australia. (15th October 2020) - Driscoll, A.; Hinde, S.; Harrison, A.; Bojke, L.; Doherty, P.
Abstract: Background: Cardiac rehabilitation (CR) programs are effective in reducing cardiovascular mortality and readmissions. However, most patients are denied the benefits of CR due to low referral rates. Of those patients referred, commencement rates vary from 28.4% to 60%. This paper quantifies the scale of health loss in Australia due to poor engagement with the program, and estimates how much public funding can be justifiably reallocated to address the problem. Methods: Economic decision modelling was undertaken to estimate the expected lifetime health loss and costs to Medicare. Key parameters were derived from Australian databases, CR registries and meta-analyses. Population health gains associated with uptake rates of 60%, and 85% were calculated. Results: CR was associated with a 99.9% probability of being cost-effective, even at a cost-effectiveness threshold lower than conventionally applied. Importantly, an average of 0.52 years of life expectancy are lost due to national uptake being below 60% achieved in some best performing programs in Australia, equivalent to 0.28 quality adjusted life years. The analysis indicates that 12.9 million/year could be justifiably reallocated from public funds to achieve a national uptake rate of 60%, while maintaining cost-effectiveness of CR due to the large health gains that would be expected. Conclusion: CR is a cost-effective service for patients with coronary heart disease. In Australia, less than a third of patients commence CR, potentially resulting in avoidable patient harm. Additional investment in CR is vital and should be a national priority as the health gains for patients far outweigh the costs. Highlights: Cardiac rehabilitation (CR) is effective in reducing mortality and readmissions. Most patients are denied the benefits of CR due to low referral rates. In this economic analysis, CR was cost-effective with a mean ICER of 6096/QALY. Patients in CR programs experience greater health benefits over a lifetime. 60% uptake of CR will lower readmissions by 823 events and 536 deaths over 10 years.